The Implementation of Cooperative Learning Method for Arabic Language Learning - Noor, Fatwiah; Jainah, Nor; Anwar, M.; Darmawaty, Ridha; Muhmood, Mostafa Farouk Abdelaleem (Institut Agama Islam Negeri Curup, 2023)
The purpose of the study was to investigate the progress of improving student learning outcomes by using cooperative learning methods. Changes in the educational paradigm require teachers to be able to provide meaningful learning and and make students the focus of learning.Â The selection of learning methods that are in lineÂ with the educational paradigm is a must. It is supposed to that the learning objectives can be achieved optimally. Implementation of learning Arabic at MTs. Sheikh Khalid was found by the author only use the lecture method and the media used was only a blackboard. The problem faced is the lack of motivation, boredom and lack of enthusiasm in participating in learning activities which causes low student learning outcomes and learning objectives are not achieved. Therefore, researchers offer cooperative learning methods as a solution to these problems due to the fact that this method directs students to be active and independent in the learning process. In this study, researchers used quantitative quasi-experimental methods. The research sample is a saturated sample. Therefore, the population in this study was all class IX MTs Sheikh Khalid. The result shows that cooperative learning method is a method that is compatible with the new educational paradigm, namely the SCL approach. This can be seen from the focus of learning which is centered on student activity. Therefore, the teacher's role as a facilitator is no longer the only source of learning for students. Another finding of this research shows that cooperative learning with its various types is able to respond to the changing paradigm of education with the SCL approach.